Case report: Successful treatment of an anti-D2R and DPPX antibody-associated autoimmune encephalitis patient with high-dose methylprednisolone and intravenous immunoglobulin - Lin, Zhangliang; Zhou, Feng; Ni, Lili; Dong, Shiye; Fu, Guoping; Zhao, Jiangman (Frontiers in Immunology, 2024)
Background: Autoimmune encephalitis is a neurological condition caused by abnormal immune responses, manifesting as cognitive impairments, behavioral abnormalities, and seizures. Its diagnosis depends on the detecting neuronal surface antibodies in serum or cerebrospinal fluid. Despite recent advances in understanding, clinical recognition remains challenging, especially with rare antibodies such as anti-dopamine D2 receptor (D2R) and anti-dipeptidyl-peptidase-like protein 6 (DPPX) antibodies. Delayed diagnosis can lead to severe complications. This case presentation emphasizes the diagnostic intricacies and effective treatment of the anti-D2R and DPPX antibody associated autoimmune encephalitis.The patient presented with a 3-day history of fatigue and limb soreness followed by a 3-hour episode of confusion and limb convulsions . Upon admission to our facility, the initial diagnosis included status epilepticus, aspiration pneumonia, metabolic acidosis, respiratory alkalosis and suspected encephalitis. Despite receiving anti-epileptic, anti-infection and anti-virus therapy, the patient's condition deteriorated. Both computed tomography (CT) scan and magnetic resonance imaging (MRI) of the brain showed no significant abnormalities. No pathogen was identified in the cerebrospinal fluid (CSF). However, further CSF and serum examination revealed positive results of anti-D2R and anti-DPPX antibodies, confirming a diagnosis of anti-D2R and DPPX antibody associated autoimmune encephalitis. The patient underwent a comprehensive treatment regimen, including high-dose methylprednisolone pulse therapy combined with intravenous immunoglobulin (IVIG), antiviral and anti-infection treatments, as well as antiepileptic medications. Significant clinical improvement was observed, and by the 18th day of admission, the patient was stable and coherent.The current patient represents the first reported case of double positive autoimmune encephalitis for anti-D2R and DPPX antibodies, with epilepsy as a prominent feature. High-dose